Peningkatan Hasil Belajar Ilmu Pengetahuan Sosial Tentang “Kegiatan Ekonomi Dan Sumber Daya Alam” Melalui Pendekatan Kontekstual - Nurwiyanti Nurwiyanti (Jurnal Lingkar Mutu Pendidikan, 2021)
The purpose of this study is to improve social studies learning outcomes in the material "Economic Activities and Natural Resources" through a contextual approach in class V SDN Tanah Tinggi 09 Pagi, Central Jakarta. This research is a classroom action research conducted in two cycles. The results of the evaluation prove that after taking action in the first cycle, social studies learning outcomes have only reached 68.83%. The research target in the first cycle has not been achieved so that the research continues to the second cycle. The results of the data analysis in the second cycle, showed an increase in student learning outcomes from 68.83% in the first cycle to 82.17% in the second cycle. From the results of this study, it can be concluded that the use of a contextual approach in learning activities can improve social studies learning outcomes about "Economic Activities and Natural Resources" in class V SDN Tanah Tinggi 09 Pagi, Central Jakarta